Mobility and IoT for the Smart Cities - Hernández-Callejo, Luis; Nesmachnow, Sergio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book compiles relevant expanded versions of the best articles presented at the Second Ibero-American Congress of Smart Cities (ICSC-CITIES 2019), published in the Special Issue "Mobility and IoT for the Smart Cities" in Smart Cities, MDPI. This book includes articles on urban mobility, as well as on integrated sensors in cities, two relevant subjects related to the development of modern smart cities moving towards sustainability.